S100-alarmins, antenatal corticosteroids and the risk of late-onset sepsis in preterm infants: A prospective cohort study - Gloria Kessler; Thomas Ulas; Thomas Vogl; Johannes Roth; Fenja Albrecht; Gesine Hansen; Constantin S. von Kaisenberg; Christoph Härtel; Bettina Bohnhorst; Dorothee Viemann; Sabine Pirr (PLoS ONE, 2026)
Objectives Antenatal corticosteroids (aCS) are an important measure improving the outcome of preterm infants. Their influence on late-onset sepsis (LOS) risk remains inconclusive. The alarmin S100A8/A9 protects from LOS by regulating innate immune responses. We examined whether aCS impact on postnatal S100A8/A9 serum-levels and consequently on LOS risk. Study design In a prospective birth-cohort study of 162 preterm infants born before 32 gestational weeks, we determined postnatal S100A8/A9 serum-levels in relation to the timing of aCS and LOS incidence. Results aCS administration within 7 days before birth decreased LOS incidence in infants born via primary C-section compared to infants not exposed to aCS (5/69 (7.2%) vs. 4/27 (14.8%)). This effect was linked to increased S100A8/A9 levels, with nocturnal aCS administration being most effective. Opposite, S100A8/A9 levels were lower and the LOS incidence higher compared to unexposed infants (7/23 (30.4%) vs. 4/27 (14.8%)) when aCS were administered more than 14 days before delivery. Conclusion Our data suggest that aCS administration affects the risk of LOS in preterm infants in dependence of the timing of administration by influencing the infant’s S100A8/A9 levels. This underlines the importance of optimal timing of aCS facing imminent preterm birth.